Benzo(a)pireno, carbamato de etila e metanol em cachaças - Miriam Solange Fernandes Caruso; Letícia Araujo Farah Nagato; Janete Alaburda (Química Nova, 2010)
The objective of this work was to evaluate the presence of benzo(a)pyrene (BaP), ethyl carbamate (EC) and methanol in 61 samples of cachaça. The quantification of BaP was carried out using HPLC with fluorescence detection, EC concentrations was determined by GC/MS and that of methanol, by GC/FID. In all samples, the concentration of methanol remained below 5 mg 100 mL-1 absolute alcohol. The results of BaP varied from <0.03 to 0.86 μg L-1; the values of EC exceeded the limit established by Brazilian legislation (150 μg L-1) in 53% of the samples.